The Ultimate Owner of Environmental, Social, and Governance Investment - Keeley, Alexander R.; Li, Chao; Takeda, Shutaro; Gloria, Tom; Managi, Shunsuke (Frontiers in Sustainability, 2022)
The coronavirus (COVID-19) pandemic has affected society in immeasurable ways, including investment. As the pandemic has impacted society’s values, it has proven to be a major turning point for environmental, social, and governance (ESG) investment. This investment approach, which evaluates a company’s ESG ratings alongside traditional financial metrics, was already “coming off a banner year,” and its reach continues to expand. Although numerous studies have investigated the impact of ESG scores on financial returns and the trend in ESG investment strategies, only a limited number of studies have attempted to capture the key players in ESG investment. Therefore, to determine the most influential investors in the ESG investment field, the cumulative impacts are calculated based on the ESG scores of invested companies, the total market price of invested companies, and the investor history portfolio report. We perform an iteration of calculation to convey the impacts that the invested companies have on the ultimate investors, and we identify the major players in the field and differences in the trend by type of investor and country.